A simplified fluorescent lateral flow assay for melamine based on aggregation induced emission of gold nanoclusters. (15th August 2022) - Yue, Xin; Pan, Qiuli; Zhou, Jie; Ren, Hongxin; Peng, Chifang; Wang, Zhouping; Zhang, Yi
Graphical abstract: Highlights: A novel LFA was designed based on the AIE of AuNCs for the detection of melamine. Molecular docking analysis verifies melamine has the highest affinity toward ATT. The sensor could discriminate 1.0 μM melamine clearly by the naked eyes within 3 min. Abstract: A novel lateral flow assay (LFA) was developed based on the aggregation induced emission (AIE) of gold nanoclusters (AuNCs) for the detection of melamine. We compared the interaction between melamine and AuNCs prepared with 6-Aza-2-thiothymine (ATT) and its four structural analogs as ligands and found that the ATT-AuNCs showed the best AIE induced by melamine. Then the ATT-AuNCs were directly immobilized on the test line of LFA strips as reporters. The sensing platform exhibited a linear response to melamine from 1 to 100 μM (R 2  = 0.997) with a detection limit of 217 nM. Moreover, this LFA strip could discriminate 1.0 μM melamine clearly by the naked eyes within 3 min. The recoveries of 91.6–101.5% were attained in milk and baby formula samples. This strip inherited the superior characteristics of low background interference of aggregation-induced fluorescence recognition and LFA technology, thus effectively avoiding the use of antibodies, aptamers, and other biological elements.